The Implementation of Padlet to Foster EFL Students’ Achievement in Writing - Sehuddin, Muh. Farid; Noni, Nurdin; Jabu, Baso (EduLine: Journal of Education and Learning Innovation, 2021)
This study is the quasi experimental research that aimed to know the effect of the implementation of Padlet to the studentsâ€™ achievement in writing. The implementation Padlet as independent variables and the studentsâ€™ achievement in writing as a dependent variable. The population in this research is all students class XI MIA MAN 1 Makassar that consist of eight classes. Class XI MIA 5 as a control group that consist of 30 students and class XI MIA 1 as an experiment group that consist of 30 students. The data of the research was obtained by the study results test on the subject of the velocity reaction for pre-test and post-test. The data was analyzed by writing test. Based on analysis of inferential statistics for writing achievement, the P = 0.001, and it less than ï¡ = 0,05 was obtained, it is means that the implementation Padlet is significantly influence to the studentsâ€™ achievement in writing of the studentsâ€™ class XI MIA 1 MAN I Makassar on the material subject of writing.